2014
DOI: 10.1021/ez500168r
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Persistence of Dispersants following the Deepwater Horizon Oil Spill

Abstract: During the 2010 Deepwater Horizon (DWH) oil spill, 1.84 M gallons of chemical dispersant was applied to oil released in the subsurface and to oil slicks at the surface. We used liquid chromatography with tandem mass spectrometry to quantify the anionic surfactant DOSS (dioctyl sodium sulfosuccinate) in samples collected from environments known to contain oil persisting from the DWH oil spill. DOSS was found to persist in variable quantities in deep-sea coral communities (6−9000 ng/g) 6 months after the spill a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 30 publications
4
77
1
Order By: Relevance
“…These findings suggest that the lasting benthic impact of deep-sea spills may be minimized by measures that drive oil to stay suspended in smaller droplets for longer-an intended mode of action of the 2.9 × 10 6 L of chemical dispersant applied directly at the wellhead during the spill. While it is not known to what extent dispersant drove oil into microdroplets that biodegraded while remaining suspended in the ocean's interior, the identification of the dispersant's active ingredient in the deep ocean intrusion layers (6) and in benthic oil deposits (4) suggests that the dispersant did remain in suspension with the oil. Furthermore, roller-tank experiments with Macondo oil (19) demonstrated that dispersant delayed the formation of marine snow, perhaps through a direct influence on the surface-layer properties of oil particles or an effect on the microbial release of aggregation-promoting exudates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that the lasting benthic impact of deep-sea spills may be minimized by measures that drive oil to stay suspended in smaller droplets for longer-an intended mode of action of the 2.9 × 10 6 L of chemical dispersant applied directly at the wellhead during the spill. While it is not known to what extent dispersant drove oil into microdroplets that biodegraded while remaining suspended in the ocean's interior, the identification of the dispersant's active ingredient in the deep ocean intrusion layers (6) and in benthic oil deposits (4) suggests that the dispersant did remain in suspension with the oil. Furthermore, roller-tank experiments with Macondo oil (19) demonstrated that dispersant delayed the formation of marine snow, perhaps through a direct influence on the surface-layer properties of oil particles or an effect on the microbial release of aggregation-promoting exudates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study questions the efficacy of the subsea dispersant application in modulating droplet size (55), and the variable impacts of dispersant on biodegradation are at the center of an ongoing debate (56,57). The effect of dispersant itself on the benthos is not well understood, but components of dispersant have been found to persist in sediments and in fragile deep-sea coral communities on a scale of years (4). Decisions regarding the use of dispersant in future spills thus need to weigh not only endpoint hydrocarbon concentration but also context: The net environmental impact of years-long exposure to high local concentrations of undispersed sediment-bound oil may or may not be more severe than the combined effects of short-term exposure of the deep water column to microdroplets of oil and dispersant and long-term exposure of sediments to their residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This early stress response was strongest in response to dispersed oil at the targeted test concentration (25 mg mL -1 ). While predicting point concentrations of oil and dispersant during a spill is difficult, impact assessments of oil spills should consider the effects of prolonged exposure to both oil and the diluted toxicants used in the chemical dispersion of oil (Goodbody-Gringley et al, 2013;White et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…At this site, most colonies were at least partially covered in a brown flocculent material that contained traces of oil from the Macondo well (White et al 2012a, Hsing et al 2013. Subsequent work on material removed from the corals showed that it also contained dioctyl sodium sulfosuccinate, a compound diagnostic of the dispersant deployed during the spill (White et al 2014). In 2011, 2 additional affected communities were discovered (Fisher et al 2014).…”
Section: Introductionmentioning
confidence: 97%